Building Sustainable Character through Community-Based Environmental Education - S Kapatan Inda Robby; M Karmilah (International Journal of Integrative Sciences, 2023)
This study aimed to investigate the effectiveness of community-based environmental education programs in promoting sustainable character development among participants. The research utilized a mixed-methods approach, consisting of both quantitative and qualitative data collection and analysis. The sample consisted of 50 individuals aged 18-30 who had participated in community-based environmental education programs within the past year. The results showed a significant improvement in participants' attitudes, knowledge, and behaviours related to sustainability after participating in the community-based environmental education programs. Qualitative data from the interviews provided further insights into the specific aspects of the program that were most impactful for participants. The findings support the effectiveness of community-based environmental education programs in promoting sustainable character development among participants and highlight the importance of creating inclusive and diverse learning environments that recognize and value different perspectives and experiences related to sustainability issues. Future research should continue to explore the long-term impacts of community-based environmental education programs on participants' behaviour and attitudes towards sustainability, as well as the broader societal and environmental benefits of these programs